2012
DOI: 10.1007/s10661-012-2948-7
|View full text |Cite
|
Sign up to set email alerts
|

Tropical storm off Myanmar coast sweeps reefs in Ritchie’s Archipelago, Andaman

Abstract: The reefs in some islands of Andaman and Nicobar suffered severe damage following a tropical storm in the Bay of Bengal off Myanmar coast during 13-17 March 2011. Surveys were conducted at eight sites in Andaman, of which five were located in the Ritchie's Archipelago where maximum wind speeds of 11 ms -1 was observed; and three around Port Blair which lay on the leeward side of the storm and had not experienced wind speeds of more than 9 ms -1 . Corals in the shallow inshore reefs were broken and dislodged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…The Andaman and Nicobar Islands face various threats to their aquatic ecosystems due to natural disasters [63][64][65]. The climate-related impacts could also pose a threat to species diversity, particularly on a small island like Car Nicobar.…”
Section: Discussionmentioning
confidence: 99%
“…The Andaman and Nicobar Islands face various threats to their aquatic ecosystems due to natural disasters [63][64][65]. The climate-related impacts could also pose a threat to species diversity, particularly on a small island like Car Nicobar.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the tropical storm's impact on reefs in Ritchie's Archipelago, Andaman, revealed that reefs suffered severe damage following the storm's passage. Also, high waves and increased sediment load by surface run-off caused significant damage to reefs in shallow and deeper regions (Krishnan et al, 2013).…”
Section: Impact Of Tropical Cyclone Ockhi On the Marine Fishery Resou...mentioning
confidence: 99%
“…In case of ANI, marine ecosystems that support fisheries such as coral reefs, mangroves and sea grass beds were seriously impacted by events such as increased sea surface temperature, tsunamis, earthquake, cyclones, storm surges etc. (Roy and Krishnan 2005;Krishnan et al 2011Krishnan et al , 2012Sachithanandam et al 2014;Yuvaraj et al 2015;Majumdar et al 2018). Coral reefs, mangroves and sea grass beds harbour major fish diversity of ANI (Rajan et al 2013) hence any impact on these ecosystem can adversely affect the fish diversity of these ecosystems ultimately affecting fishermen who are dependent on these ecosystems for livelihood and income generation.…”
Section: Natural Calamities and Extreme Eventsmentioning
confidence: 99%